Estimation of drug consumption in Kuantan, Pahang, Malaysia via wastewater-based drug epidemiology - Mohammad Azimuddin, Izani; Nurul `Azyyati, Sabri; Khaw, Kooi Yeong; Iekhsan, Othman; Tay, Joo Hui (The Malaysian Analytical Sciences Society, 2024)
The wastewater-based drug epidemiology (WBDE) methodology has been extensively employed to estimate drug consumption in diverse communities worldwide, serving as a valuable supplement to conventional epidemiological approaches. However, such methodology has not been employed to study drug consumption rates in the East Coast of Peninsular Malaysia. In this study, we aimed to estimate drug consumption rates in Kuantan, Pahang utilizing the WBDE methodology. Untreated wastewater samples were collected from the 14 largest wastewater treatment plants (WWTPs) in Kuantan between August and November 2021. Excreted residues of amphetamine (AMP), methamphetamine (METH), 3,4-methylenedioxy methamphetamine (MDMA), 3,4-methylenedioxyamphetamine (MDA), and morphine (MOR) were analyzed using liquid chromatography coupled with triple quadrupole mass spectrometry. AMP, METH, MDMA and MDA were detected at mean concentrations ranging from below detection limit (<LOD) to 1890 ng/L, while MOR was not found in any of the samples. METH was the most prevalent illicit drug in Kuantan, with a total estimated mean consumption rate of 7.04 mg/day/1000 people. Although the estimated consumption rate may not be directly comparable to other research due to the decentralized design of WWTPs in the studied area, our findings have provided insights into hotspots and/or high-risk areas for drug usage in the serviced community and a deeper understanding of METH and MDMA consumption patterns across different WWTPs. This information would be valuable for local authorities in planning targeted solutions to address these issues.